2007
DOI: 10.1210/en.2006-0991
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Inhibits Apoptosis in Hypothalamic Neuronal Cells during Oxygen-Glucose Deprivation

Abstract: Ghrelin is an endogenous ligand for the GH secretagogue receptor, produced and secreted mainly from the stomach. Ghrelin stimulates GH release and induces positive energy balances. Previous studies have reported that ghrelin inhibits apoptosis in several cell types, but its antiapoptotic effect in neuronal cells is unknown. Therefore, we investigated the role of ghrelin in ischemic neuronal injury using primary hypothalamic neurons exposed to oxygen-glucose deprivation (OGD). Here we report that treatment of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
149
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(176 citation statements)
references
References 82 publications
25
149
0
2
Order By: Relevance
“…18 In addition, ghrelin has several antiinflammatory properties and decreases neuronal apoptosis. [19][20][21][22] Antioxidant properties of ghrelin have also been demonstrated in recent studies. [23][24][25] Therefore, the aim of this study was to evaluate the effects of ghrelin on the blood levels of MDA and TAC and brain levels of MDA, SOD, GPx and CAT in the normobaric systemic hypoxia situation in rats.…”
Section: Introductionmentioning
confidence: 82%
“…18 In addition, ghrelin has several antiinflammatory properties and decreases neuronal apoptosis. [19][20][21][22] Antioxidant properties of ghrelin have also been demonstrated in recent studies. [23][24][25] Therefore, the aim of this study was to evaluate the effects of ghrelin on the blood levels of MDA and TAC and brain levels of MDA, SOD, GPx and CAT in the normobaric systemic hypoxia situation in rats.…”
Section: Introductionmentioning
confidence: 82%
“…Neuroprotective effects of ghrelin have been recently reported in rodent model of focal cerebral ischemia (Chung et al 2007, Miao et al 2007, in which systemic administration of ghrelin augmented the expression of Bcl2/Bax and heat shock protein 70 and inhibited prostate apoptosis response-4, caspase-8, -9, and -3. In addition, we demonstrated the in vitro neuroprotective effect of ghrelin in neurons, which was associated with the inhibition of the apoptotic cascade and preservation of mitochondrial integrity (Chung et al 2007(Chung et al , 2008.…”
Section: Discussionmentioning
confidence: 98%
“…injection of ghrelin (80 mg/kg) 30 min prior to KA injection, and a second ghrelin treatment was performed 24 h after the KA injection. In this study, 80 mg/kg of ghrelin was chosen on the basis of our previous studies that this dose of ghrelin exerted a potent neuroprotective action (Chung et al 2007). To examine whether the effect of ghrelin is exerted through GHSR1a, animals were co-treated with D-Lys-GHRP-6 (1 mg/kg, i.p.)…”
Section: Animals and Drug Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we demonstrated that rats treated with GH or GHRP-6 showed increased levels of phosphorylated Akt but not of ERK1/2 in the hypothalamus, hippocampus and cerebellum (Frago et al 2002); although in some circumstances, GH and ghrelin have been shown to activate not only the PI3K/Akt signalling pathway but also the MAPK pathway (Chung et al 2007, Brooks et al 2008, Andrews 2011. Thus, GH after binding to its receptor activates the PI3K/Akt signalling pathway (Frago et al 2002), which could induce the activation and differentiation of astrocytes in the hypothalamus and hippocampus.…”
Section: Discussionmentioning
confidence: 93%